2016
DOI: 10.4322/1984-3143-ar726
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of fruit-juices on sperm viability of West African Dwarf goat bucks during cryopreservation

Abstract: The present study was conducted to determine the effects of adding fruit-juices to semen extenders on viability of buck spermatozoa during cryopreservation in two studies. Pooled semen samples obtained from West African Dwarf (WAD) goat bucks were diluted with Tris-egg yolk based extenders. In study I, the diluted semen samples were supplemented with orange (Citrus sinensis), cucumber (Cucumis sativus) and pineapple (Ananas comosus) juices (2.5, 5, 7.5 and 10 ml/100 ml). In study II, the diluted semen samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
3
0
3
Order By: Relevance
“…The study carried out by Fukuhara and Nishikawa (1973) (28) showed a significant effect of increasing energy to maintain motility in goat sperm when a variety of sugars was added, but there was no significant difference caused by sucrose, unlike glucose and fructose, which promoted improvements. Daramola et al (2016) (16) , studying cucumber, pineapple and orange juices added to cryopreserved ram semen diluent, found higher values of progressive motility, especially when using concentrations of 7.5 and 10%. In the present study, pineapple and orange juices did not produce similar results, unlike beet juice, which was statistically better regarding progressive motility than the others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study carried out by Fukuhara and Nishikawa (1973) (28) showed a significant effect of increasing energy to maintain motility in goat sperm when a variety of sugars was added, but there was no significant difference caused by sucrose, unlike glucose and fructose, which promoted improvements. Daramola et al (2016) (16) , studying cucumber, pineapple and orange juices added to cryopreserved ram semen diluent, found higher values of progressive motility, especially when using concentrations of 7.5 and 10%. In the present study, pineapple and orange juices did not produce similar results, unlike beet juice, which was statistically better regarding progressive motility than the others.…”
Section: Discussionmentioning
confidence: 99%
“…The juices were prepared according to the procedures described by Adeyemo et al (2007) (15) and Daramola et al (2016) (16) from pineapple (Ananas comosus L. var. Pearl), sweet orange (Citrus sinensis L.) and beet (Beta vulgaris L).…”
Section: Preparation Of Fruit and Beet Juicesmentioning
confidence: 99%
“…O mesmo tratamento também manteve o percentual de motilidade total acima de 30%, em linha com as características desejáveis para carneiros quanto à dose de sêmen congelado segundo o CBRA (2013) (21) . Os açúcares podem promover melhorias no equilíbrio osmótico e na crioproteção das células espermáticas, além de serem utilizados na ocorrência de fosforilação oxidativa (9,16) . Wruss et al (2015) (27) , ao analisarem o suco de sete diferentes variedades de beterraba, encontraram valores entre 60% de betacianinas e 40% de betaxantinas, que representaram de 70 a 100% do total de compostos fenólicos.…”
Section: Discussionunclassified
“…Daramola et al (2016) (16) , estudando sucos de pepino, abacaxi e laranja adicionados ao diluente de sêmen ovino criopreservado, encontraram maiores valores de motilidade progressiva, principalmente quando se utilizaram concentrações de 7,5 e 10%. No presente estudo, os sucos de abacaxi e laranja não obtiveram resultados semelhantes, diferentemente do suco de beterraba, que foi estatisticamente melhor em motilidade progressiva que os demais.…”
Section: Discussionunclassified
See 1 more Smart Citation